Entomobrya (Collembola, Entomobryidae) for the Canary Islands - Baquero, Enrique; Jordana, Rafael (Zootaxa, 2018)
This paper examines a single genus of springtails (Collembola, Entomobryidae, Entomobrya) across the Canary Islands archipelago. A great sampling effort carried out more than 20 years ago, and over several years, allows us to present the distribution of the genus with the presence of 17 species, some better represented by their abundance than others. In addition to some species present in continental Europe or elsewhere in the world, or those already reported for the Canary Islands (e.g., E. multifasciata (Tullberg, 1871), E. nigrocincta Denis, 1923, E. palmensis Jordana & Baquero, 2010, E. quinquelineata Börner, 1901 and E. unostrigata Stach, 1930), 12 new species have been detected and described, representing 71% of the total species found. All new species have been named in honour of important persons to the history of the Canary Islands, including some leaders. A combination of colouring patterns and other morphological characteristics that are easy to observe in most specimens (Katz et al. 2015a, b) have been used for the identification of the specimens, as is usual for the genus (Christiansen 1958), in addition to the dorsal macrochaetotaxy formula proposed by Jordana & Baquero (2005). Without this formula, many specimens could not have been identified or distinguished from already described species because the colourations —in many cases—show ranges so broad as not to be diagnostic. In some species, the range of colouration can range from totally clear to totally dark, including several intermediate forms. Colour could be a good indicator of the species captured, taking into account that it fades over time with exposure to ethyl alcohol and could turn to different tones. Notwithstanding the above, a recent paper by Ding et al. (2018), show a certain correlation between the color pattern and the specific differentiation by means of DNA studies.